CONCEPTUAL AND INFORMATION APPROACH TO THE DESIGN OF BUILDINGS, TAKING INTO ACCOUNT THE TECHNICAL SOLUTIONS AT THE STAGES OF ITS LIFE CYCLE - S. V. Shilkina (Современная наука и инновации)
Information modeling of buildings is associated with the process of creating and using information about the object of research, which forms the basis for all solutions throughout its life cycle from the idea of the project to the design, construction, operation, reconstruction and demolition of the structure.